2015
DOI: 10.1074/mcp.m114.043141
|View full text |Cite
|
Sign up to set email alerts
|

Acetylome Profiling Reveals Overlap in the Regulation of Diverse Processes by Sirtuins, Gcn5, and Esa1

Abstract: Although histone acetylation and deacetylation machineries (HATs and HDACs) regulate important aspects of cell function by targeting histone tails, recent work highlights that non-histone protein acetylation is also pervasive in eukaryotes. Here, we use quantitative mass-spectrometry to define acetylations targeted by the sirtuin family, previously implicated in the regulation of non-histone protein acetylation. To identify HATs that promote acetylation of these sites, we also performed this analysis in gcn5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 61 publications
6
77
3
1
Order By: Relevance
“…levels of these marks in vivo (Zhang et al 1998;Howe et al 2001;Pray-Grant et al 2005;Downey et al 2015). We asked if RTS1 mediated restoration of H3 acetylation.…”
mentioning
confidence: 99%
“…levels of these marks in vivo (Zhang et al 1998;Howe et al 2001;Pray-Grant et al 2005;Downey et al 2015). We asked if RTS1 mediated restoration of H3 acetylation.…”
mentioning
confidence: 99%
“…Since cells lacking HST3 and HST4 are reported to display increased sensitivity to DNA damaging agents (Celic et al 2006;Maas et al 2006), we reasoned that the positive effects of nicotinamide observed in our assays were likely due to inhibition of the remaining sirtuins, Hst1, Hst2, and Sir2, which impact the acetylation status of many proteins within the cell (Downey et al 2013(Downey et al , 2015Downey and Baetz 2016). However, an hst1D hst2D sir2D triple mutant failed to phenocopy treatment with nicotinamide ( Figure 1B).…”
Section: Nicotinamide Suppresses Mms Sensitivity Independently Of Sirmentioning
confidence: 84%
“…Since we previously found that multiple sirtuins regulate acetylations on the same substrates (Downey et al 2013(Downey et al , 2015, we used nicotinamide to inhibit these enzymes as a group ( Figure 1A). We found that plates that included nicotinamide at a concentration of 5 mM allowed for increased growth in the presence of high concentrations of MMS (i.e., 0.03% and above; Figure 1B).…”
Section: Nicotinamide Enhances Mms Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it acts on nonhistone substrates, such as the NuA4 subunits Epl1 and Yng2 (7,12), the autophagy protein Atg3 (13), the RNA processing protein Nab3 (14,15), and nearly 200 other proteins (12,15,16). Notably, the Tip60 human ortholog of Esa1 has been linked to multiple human diseases (17)(18)(19), thus increasing the relevance of gaining a deeper understanding of Esa1 functions.…”
mentioning
confidence: 99%